Morbidity Profile of Workers in Brick Kilns under a Gram Panchayat, South India - C J Navya; Deepthi Shanbhag; R Naveen; S Swathi; Laviena M; T Krupa (Medsci Publications, 2017)
Introduction: Brick Industry in India is a small scale industry which employs large number of migrant workers from rural areas. The stress at the work place, long hours of work and poor environmental conditions in and around brick making units have an impact on the workers health. Objective: To assess the morbidity profile of workers in brick kilnsina Gram Panchayatarea in Karnataka. Methods: A pre designed and structured interview schedule was used to collect data with physical examination and pulmonary function testing using Wright Peak Flow Meter (PEFR) was done. Data was analyzed using SPSS Version 16. Results: Most Common morbidities identified were musculoskeletal pain (48%), under weight (31%), respiratory diseases (27%), skin diseases (12%), eye complaints (8%) and work place injuries (5%).Prevalence of tobacco use was 67%.78% of the workers had PEFR less than normal even though there was no statistically significant association between PEFR and respiratory morbidity or duration of work. There was no provision of personal protective equipments (PPE) in any of these factories. Conclusion: An improvement of working environment, residential quarters and enforcement of safety devices are needed in the factories studied. Pre-placement and periodic examination should be done to identify at risk individuals.